Φ, Ψ-Weak Contractions in Neutrosophic Cone Metric Spaces via Fixed Point Theorems. (29th July 2020) - Al-Omeri, Wadei F.; Jafari, Saeid; Smarandache, Florentin
Abstract : In this manuscript, we obtain common fixed point theorems in the neutrosophic cone metric space. Also, notion of Φ, Ψ -weak contraction is defined in the neutrosophic cone metric space by using the idea of altering distance function. Finally, we review many examples of cone metric spaces to verify some properties.